2000
DOI: 10.1063/1.126964
|View full text |Cite
|
Sign up to set email alerts
|

Electron drift mobility in pyrazolo[3,4-b]quinoline doped polystyrene layers

Abstract: Pyrazolo[3,4-b]quinoline derivatives are found to have electron transport properties. A field dependent electron drift mobility, in the range of 10−6–3×10−5 cm2/(V s) at an electric field of (1–7)×105 V/cm, has been found from the pyrazolo[3,4-b]quinoline doped polystyrene specimen, which was measured using a conventional time-of-flight method. The results are fit well into a correlated disorder model for a dipole medium when energetic features of the transport molecules are also taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The ®eld dependent mobility of PAP2 was then further investigated at different temperature as seen in Figure 3 and the mobility increases as the temperature is raised. It has been demonstrated that the correlated disorder model (CDM) [3] appeared to be a suitable model to describe the dependence of mobility on the applied electric ®eld from our previous study [1]. The CDM takes into account the dipole nature of the medium and leads to the following relationship describing non-dispersive mobility [3]:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ®eld dependent mobility of PAP2 was then further investigated at different temperature as seen in Figure 3 and the mobility increases as the temperature is raised. It has been demonstrated that the correlated disorder model (CDM) [3] appeared to be a suitable model to describe the dependence of mobility on the applied electric ®eld from our previous study [1]. The CDM takes into account the dipole nature of the medium and leads to the following relationship describing non-dispersive mobility [3]:…”
Section: Resultsmentioning
confidence: 99%
“…Layered sandwich specimens (378 mm in thickness) were prepared for TOF experiment as previously described [1]. The drift mobility m was determined from the expression m d=F Á t T , where F is the applied ®eld and d is the thickness of carrier transporting layer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41] Our recent work revealed a potential use of 1-phenyl-3,4-dimethyl-1H-pyrazolo [3,4-b]quinoline (PAQ5) as an emitter dopant to stabilize the colour characteristics. [36] Stable light emission is particularly important in display devices for generating a basic colour.…”
Section: Introductionmentioning
confidence: 99%
“…PAQ4 and a few other pyrazoloquinoline and bispyrazolopyridine derivatives were found to have field-dependent electron mobilities in the range of 10 À6 -10 À4 (cm 2 V À1 s À1 ) when dispersed in a polystyrene matrix. [3,4] Coupled with their carrier transporting properties, pyrazoloquinoline and bispyrazolopyridine derivatives have been investigated to use in electroluminescent devices [2,5,6]. Copolymers with pyrazol moieties as main chains or side chains were also prepared [7].…”
Section: Introductionmentioning
confidence: 99%